A Study of Research Information Management Systems in Iran: The Production of Validation Tools - Manouchehr Karami; Payam Kabiri; Farzaneh Fazli; Nahid Ramezanghorbani (Tehran University of Medical Sciences, 2022)
Background and Aim: One of the most important challenges in the field of research information management is the use of reliable and qualified software to manage research resources in health domain. This study aimed to develop a validation tools for research information management systems in Iran to utilize by universities in the process of using existing research information management systems. Materials and Methods: This was a descriptive study conducted in two stages. In the first stage, a validation tool for research information management systems (Pajoohan, Pajooheshyar, Jiro, Yektaweb, Kuiper) was designed, and in the next stage, in order to ensure the validity of the produced tool, a self-assessment survey was conducted by users of research information management systems in medical sciences universities. Therefore, this tool was completed by 104 researchers from all over the country. The collected data were analyzed by Excel and SPSS software. Results: The developed validation tool of research information management systems included four components and 82 indicators: software design and architecture (17 indicators), usability and user environment (16 indicators), professional use (36 indicators) and management (13 indicators). Based on the self-declared results of the users, this tool has 57 mandatory features, 26 preferred and 4 optional features. The results of the validation of research information management systems based on this tool showed that the highest rank in the component of architecture, professional use and software management was related to the Kuiper system, and in the component of usability and user environment was related to the Pajoohan system. In the self-declaration done by the users ,12 cases of Jiro system ,11 cases of Kuiper system ,11 cases of Pajoohan system ,7 cases of Pajooheshyar, and 5 cases of Yektaweb system have received confirmation above 75%. Conclusions: The validation tool which developed by this study can be used in the evaluation of current research information management systems and the selection of new systems for use in the research field. In addition, it can be used to improve current systems and purchase new systems by academic universities and research centers.